Genetic diversity and validation of a microsatellite panel for parentage testing for alpacas (Vicugna pacos) on three Peruvian farms - Morón, J. A. (2020)
The alpaca is of greatest economic importance in the Peruvian High Andes. This study aimed to determine the genetic diversity of three Peruvian alpaca farms, as well as, to validate a microsatellite markers panel for paternity testing. In this study, 247 samples of Huacaya alpacas were taken from three different localities (Sanjo, San Pedro de Raco and Cachipampa) from Pasco Region in Peru. DNA was obtained from hair follicles and genotyped for 15 microsatellites markers in multiplex electrophoresis runs.A total of 225 alleles were detected across the 15 loci investigated. The polymorphism information content considering all loci was 0.82, which indicated that the microsatellite panel was very polymorphic and highly informative. The estimated diversity parameter showed that farms have high levels of genetic diversity (HE = 0.826), and revealed the existence of genetic differentiation among the farms (FST = 2.8 %). The highest inbreeding coefficient was in the Sanjo farm (FIS = 0.303). The results of the parentage testing indicated that all loci showed values greater than 70 % probability of discrimination. However, the highest values found were 94 % (YWLL08) and 90 % (YWLL36). The average of the probability of exclusion obtained was 0.999994 if the genotype for one alleged parents is known, and 0.99999 if the genotypes for both alleged parents are known. The results obtained show that there is a high genetic diversity and validate the panel of microsatellite markers, that would help to improve the identification system and genealogical data collection.